Effect of Lithium/Transition‐Metal Ratio on the Electrochemical Properties of Lithium‐Rich Cathode Materials with Different Nickel/Manganese Ratios for Lithium‐Ion Batteries. Issue 32 (27th August 2019) - Konishi, Hiroaki; Terada, Shohei; Okumura, Takefumi
Abstract: A lithium‐rich nickel‐manganese‐based material (Li1.2 Ni0.2 Mn0.6 O2 ) exhibited a high discharge capacity at a low C‐rate. However, this material has problems in that it has a poor rate performance, large potential hysteresis, and poor cycle performance. Although increasing the Ni/Mn ratio for Li1.2 Ni0.2 Mn0.6 O2 ameliorated these problems, it decreased the discharge capacity. In this study, the lithium/transition‐metal (Li/TM) ratios for lithium‐rich layer‐structured cathodes with different Ni/Mn ratios were controlled to attain a high discharge capacity, high rate performance, small potential hysteresis, and high cycle performance. For a low‐Ni/Mn‐ratio (Li1.2 Ni0.2 Mn0.6 O2 ) cathode, a decrease in the Li/TM ratio deteriorated the discharge capacity. Conversely, for cathodes with a high Ni/Mn ratio (Li1.2 Ni0.25 Mn0.55 O2 and Li1.2 Ni0.3 Mn0.5 O2 ), the decreases in the Li/TM ratios improved the discharge capacity. In addition, for the high‐Ni/Mn‐ratio cathodes, the decrease in the Li/TM ratio from 1.2/0.8 to 1.18/0.82 increased the discharge capacity at a high C‐rate (3 C) from 157 to 183 Ah kg ‐1 (Li1.2 Ni0.25 Mn0.55 O2 ) and from 139 to 156 Ah kg ‐1 (Li1.2 Ni0.3 Mn0.5 O2 ). Furthermore, the decrease in the Li/TM ratio suppressed potential hysteresis and capacity degradation during cycling for the high‐Ni/Mn‐ratio cathodes. Abstract : The discharge capacity for a conventional lithium‐rich cathode (Li1.2 Ni0.2 Mn0.6 O2 ) at a high C‐rate (3 C) was low. To improve the rate performance for the Li1.2 Ni0.2 Mn0.6 O2, the Ni/Mn and Li/(Ni+Mn) ratios were controlled. The discharge capacity at a high C‐rate was increased due to an increase in the Ni/Mn ratio (Li1.2 Ni0.25 Mn0.55 O2 ), and it was further increased due to a decrease in the Li/(Ni+Mn) ratio (Li1.18 Ni0.26 Mn0.56 O2 ).